METHODS OF GENERATING FLORESCENCE RESONANCE ENERGY TRANSFER (FRET) BETWEEN SEMICONDUCTOR QUANTUM DOTS AND FLUORESCENT DYES/PROTEINS VIA MULTI-PHOTON EXCITATION, ACHIEVING ZERO BACKGROUND OR DIRECT EXCITATION CONTRIBUTIONS TO THE FRET SIGNATURE - CLAPP, AARON, R; MEDINTZ, IGOR, L; MATTOUSSI, HEDI, M (2009)
A system and method of sensing physiological conditions in biological applications includes a laser source for optically exciting a plurality of luminescent quantum dots and a plurality of biomolecules in a nanoscale sensing system having a nanocrystal structure, where the plurality of biomolecules is stained with dye. In a multi-photon excitation process, a laser system optically excites, the plurality of luminescent quantum dots and the plurality of biomolecules in the nanoscale sensing system, where fluorescence resonance energy transfer (FRET) occurs between the plurality of quantum dots and the plurality of biomolecules. Stability of self assembly of quantum dot peptide conjugates within the plurality of biomolecules is investigated. Physiological conditions at the cellular level are determined, using a spectrometer to sense fluorosence spectra. The sensing of physiological conditions includes transducing signals into immunoassays, clinical diagnostics and cellular imaging to provide treatment to biological subjects including human patients. La présente invention concerne un système et un procédé de détection d'états physiologiques dans des applications biologiques comprenant une source laser pour exciter optiquement une pluralité de nanocristaux luminescents et une pluralité de biomolécules dans un système de détection à l'échelle nanométrique ayant une structure nanocristalline, la pluralité de biomolécules étant teintée avec un colorant. Dans un processus d'excitation multiphotonique, un système laser excite optiquement la pluralité de nanocristaux luminescents et la pluralité de biomolécules dans le système de détection à l'échelle nanométrique, où un transfert d'énergie de résonance de fluorescence (FRET) se produit entre la pluralité de nanocristaux et la pluralité de biomolécules. La stabilité de l'auto-assemblage de conjugués peptidiques nanocristallins au sein d'une pluralité de biomolécules est étudiée. Les conditions physiologiques au niveau cellulaire sont déterminées à l'aide d'un spectromètre pour détecter les spectres de fluorescence. La détection des conditions physiologiques comprend la transformation des signaux en dosages immunologiques, en diagnostics cliniques et en imagerie cellulaire pour offrir un traitement à des sujets biologiques comprenant des patients humains.